Dispositivo coletor-detector fabricado aditivamente para análise de explosivos utilizando filamento de PLA reciclado carregado com carbon black e/ou grafite - Souza, Maria Moura Cruvinel (2024)
2,4,6-Trinitrotoluene (TNT) is an explosive widely used in military activities due to its low cost and low sensitivity to mechanical impacts. It is also frequently used in terrorist attacks and criminal events, leaving residues and by-products that become key traces in forensic investigations. The methods employed by forensic experts for TNT detection are expensive and complex. Thus, there is a need to develop sensitive, low-cost, and portable methods for the rapid detection of this explosive. This work presents a 3D-printed device with a dual function: a residue collector and a TNT explosive detector using square-wave voltammetry. Two filaments produced in the laboratory from recycled polylactic acid (rPLA) and castor oil were tested. The first filament contained only carbon black (CB) as the conductive material. The second filament included graphite (Gpt) to maintain electrochemical properties while reducing production costs. Laboratory-fabricated electrodes were compared with electrodes made from commercial filament (composed of PLA and CB), demonstrating the superior electrochemical performance of the lab-produced filaments without requiring any prior treatment or activation. The electrochemical response of the redox pair [Fe(CN)₆]³⁻/⁴⁻ showed a peak-to-peak separation of 180 ± 8 mV (Gpt-CB-rPLA) and 240 ± 6 mV (CBrPLA), while the commercial electrode exhibited a separation of 740 ± 10 mV. Furthermore, the electrodes fabricated from recyclable materials displayed lower charge transfer resistance (Rct) (1040 ± 50 Ω for Gpt-CB-rPLA, 1810 ± 30 Ω for CB-rPLA, and 9620 ± 280 Ω for CB-PLA) and a higher heterogeneous rate constant (k₀) than the commercial electrode (6.91 (± 0.58) × 10⁻³ cm s⁻¹ for Gpt-CB-rPLA; 5.31 (± 0.40) × 10⁻³ cm s⁻¹ for CB-rPLA and 3.62 (± 0.38) × 10⁻³ cm s⁻¹ for CB-PLA). Calibration curves for TNT detection yielded limits of detection (LOD) of 0.88 and 3.42 μmol L⁻¹ for the Gpt-CB-rPLA and CB-rPLA electrodes, respectively, and 1.55 μmol L⁻¹ for the commercial electrode. For real sample application, a TNT explosion simulation was performed, and two methods for collecting residues were tested: point collection and friction collection. It is noteworthy that the results were achieved without electrode treatment or activation, suggesting that the rough surface of the fabricated electrode is advantageous for collecting explosive residues. This feature allows the platform to be simply rubbed against different surfaces at crime scenes.